Pemberdayaan Penyandang Disabilitas melalui Kewirausahaan Inklusif: Studi Kasus pada UMKM di Banten dan Jawa Barat - Abadi, Reza Febri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the forms and effectiveness of empowering persons with disabilities through inclusive entrepreneurship within the MSME (Micro, Small, and Medium Enterprises) sector in Indonesia, particularly in the provinces of Banten and West Java. Using a descriptive qualitative approach and a case study method, data were collected through in-depth interviews, participatory observation, and documentation involving 10 MSMEs that employ persons with disabilities, 6 individuals with disabilities, and 4 supporting organizations (NGOs/communities). The findings indicate that inclusive entrepreneurship is implemented through adaptive work access, skills training, and the strengthening of social networks. MSMEs play a strategic role as agents of social empowermentnot only by providing employment opportunities, but also by increasing the social participation of persons with disabilities. Key enabling factors include inclusive leadership from business owners, engagement from local communities, and the use of digital technology for product marketing. However, significant challenges persist, such as social stigma, limited access to business capital, and the lack of effective implementation of affirmative policies. These findings highlight the importance of collaboration among business sectors, government institutions, and civil society to build an inclusive entrepreneurial ecosystem. The study recommends the formulation of incentive policies for inclusive MSMEs, strengthening of adaptive skills training for persons with disabilities, and the establishment of sustainable public-community partnership networks. With a systemic and community-based approach, inclusive entrepreneurship can serve as an effective instrument for promoting equitable, participatory, and sustainable socio-economic development in Indonesia.